Systemic levels of C-reactive protein in patients with age-related macular degeneration: A systematic review with meta-analyses. (October 2020) - Feng, Chen; Krogh Nielsen, Marie; Sørensen, Torben Lykke; Subhi, Yousif
Highlights: Age-related macular degeneration (AMD) is the most prevalent cause of irreversible vision loss in the developed world. Chronic low-grade inflammation has been investigated due to its role in the gap between chronological and biological aging. Our systematic review summarizes 53 studies with 60, 598 on C-reactive protein (CRP), a well-established marker of systemic inflammation, in AMD. Our meta-analyses find a significant small-to-moderate increase in CRP, but only in late and neovascular forms of AMD. Abstract: Ageing of the retina is associated with the gradual accumulation of basal deposits and the formation of drusen. However, in some individuals this process is exacerbated and causes development of age-related macular degeneration. Late features of age-related macular degeneration include geographic atrophy of the neuroretina or choroidal neovascularization. Such changes lead to blurred vision, metamorphopsia, and scotoma, and is the leading cause of vision loss in developed countries. Chronic low-grade inflammation has been investigated because of its relationship to ageing and its role in the gap between chronological and biological ageing. Here, we systematically reviewed studies investigating systemic C-reactive protein in patients with age-related macular degeneration. We identified 53 studies with 60, 598 participants (10, 392 patients and 38, 901 controls). Our meta-analyses revealed that early age-related macular degeneration was not associated to systemic C-reactive protein (Cohen's d = 0.03 [−0.04 to 0.10]; OR = 1.06 [0.93–1.20]; P = 0.39) whereas late age-related macular degeneration (Cohen's d = 0.38 [0.24 to 0.51]; OR = 1.99 [1.55–2.52]; P < 0.0001), and neovascular age-related macular degeneration (Cohen's d = 0.40 [0.24 to 0.56]; OR = 2.07 [1.55–2.76]; P < 0.0001) was associated with a small-to-moderate increase in systemic C-reactive protein. Our review provides an overview of this extensively studied field, provide summary estimates that provide insight into when and to what extent systemic C-reactive protein is associated with age-related macular degeneration, and help in distinguishing the potentially reversible disease processes from that of irreversible retinal ageing.